Redes de energía y cohesión territorial. Conformación de los sistemas de transporte de electricidad y gas en Argentina - Carrizo, Silvina Cecilia (2014)
Argentina has developed wide networks of electricity and gas transport. On the one hand, the national electrical grid has been formed by the interconnection of isolated local systems and the connection of large plants with large consumption centers, later reinforced through the articulation between regional systems. On the other hand, the gas network has expanded from national pipelines, laid down from the hydrocarbon basins, to serve Buenos Aires, but also supplying the regions they cross. Natural gas has penetrated residential, industrial, electrical and automobile markets; and isolated systems have emerged even where gas pipelines do not pass. Also local electricity systems and distributed generation are reappearing. Then the opportunities to take advantage of non-conventional renewable energies arise. These open the field to new energy sector organization forms. The possibilities to access to energy are multiplying and a new geography could be delineated with a more flexible, reliable, sustainable and equitable energy circulation, encouraging innovation and productivity, and fighting against pollution and social exclusion, in a manner which could foster territorial cohesion.